Berpikir Positif dengan Efikasi Diri Akademik pada Mahasiswa yang sedang Menyusun Skripsi - Indrawati, Waode; Suarni, Waode; Herik, Eva (Jurnal Sublimapsi, 2024)
Students with low academic self-efficacy tend to avoid learning assignments, especially challenging and difficult assignments such as thesis. On the other hand, students with a high level of academic self-efficacy tend to not to avoid doing such assignments. Positive thinking is one way to increase academic self-efficacy in students. Therefore, this research was conducted with the aim of knowing the relationship beetwen positive thinking and academic self-eficacy in students who are preparing their thesist at FKIP UHO. The sampling technique used cluster random sampling, in order to obtain a totatl sample of 100 people from 2062 student populations who were preparing their at the Faculty of Teaching and Education at Halu Oleo University. The data colection method used the positive thinking scale and academic self-efficacy scale. The data analysis technique used the Pearson’s Product Moment correlation method. The research result obtained showed that there was a significant positive relationship between positive thinking and academic self-efficacy in students who were preparing their thesis at FKIP UHO.